Recursos de tecnologia digital na alfabetização de estudantes com transtorno do espectro do autismo: uma revisão sistemática - Memari, Heloise (Universidade Federal de São Carlos, 2025)
The use of digital technology resources in the educational context can be considered an effective and satisfactory practice, given that some schools face challenges in promoting the literacy of students with Autism Spectrum Disorder (ASD) through the application of traditional teaching methods. Therefore, technologies can become mediating tools in the learning process. The objective of this study was to analyze, through a literature review, the scientific production regarding the use of digital technology resources in the literacy of students with ASD. To this end, a search was conducted in three databases: the CAPES Portal of Journals (Coordination for the Improvement of Higher Education Personnel), the Scientific Electronic Library Online (SciELO), and the Brazilian Digital Library of Theses and Dissertations (BDTD). The first stage involved a bibliographic survey of articles, theses, and dissertations in the selected databases. The survey was carried out using the following search strategies: Transtorno do Espectro do Autismo and Tecnologia Digital and alfabetização, Transtorno do Espectro do Autismo and Tecnologia Assistiva and alfabetização, Autismo and Tecnologia Assistiva and alfabetização, and Autismo and Tecnologia Digital and alfabetização. The inclusion criteria required that the studies be articles, theses, or dissertations written in Portuguese, with no time frame restriction, and aligned with the topic. The variables selected for analysis were: objectives, methods, results, and conclusions, resulting in the selection of nine studies. The results obtained through the searches confirmed that digital technology resources can support the literacy process of students with ASD, considering that applications and software can assist in the development of various skills that are predictive of literacy, as well as in communication. The findings highlight the importance of further scientific research on this topic to support the work of teachers, educators, and families in the literacy of students with ASD through the use of technology, given the benefits presented.
Digital technology resources in the literacy of students with autism spectrum disorder: a systematic review
Keywords: Educação especial; Tecnologia da informação e comunicação; Alfabetização; Autismo; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL